Paternal perceptions and activities in socialization of young children in an urban community - Diaz, Joselle Therese Pascua
Previous studies have examined paternal involvement but to a limited extent only. To add on the increased knowledge on this study explored the nature of paternal involvement on the socialization of young children among the lower-class families. Particularly, this study looked on the four content areas of socialization which include transmission of values, gender role socialization, acquiring of prosocial behaviors, and development of communication. Thirty low-income fathers with children aged two to six years were drawn through purposive sampling and snowball approach from teh community of Barangay San Vicente in Quezon City. Qualitative interviews were employed to obtain the necessary data. The father's responses were then categorized and analyzed using frequencies, relative percentages, and ranking. Results indicate that the low-income fathers' socialization activities are generally influenced by their perceptions on the four areas of socialization. Data also revealed that factors such as sense of fulfillment, perceived needs of the children, and social expectations contribute to higher paternal involvement, while time availability, feelings of incompetence compared to the mothers, lower perceived needs of the children, gender-role ideology of the fathers, and the presence of other potential caregivers limit the involvement of fathers.